Recommendations for Publishing Clinical Cases - Oliveros Wilches, Ricardo; Prieto Ortiz, Robin German (Revista colombiana de Gastroenterología, 2023)
The importance of publishing clinical cases lies in the diagnostic or therapeutic developments they can contribute. This paper mainly aims to guide young doctors in writing and publishing a clinical case. Reflections are encouraged on choosing a clinical case and writing it sharply, briefly, and chronologically to improve the chances of acceptance and publication. Recommendations on how to use the CARE (Case Report Statement and Checklist) are also given.